Reply to Comment by Michael K. Tippett on "On the Relationship Between Probabilistic and Deterministic Skills in Dynamical Seasonal Climate Prediction". Issue 7 (2nd April 2019) - Yang, Dejian; Yang, Xiu‐Qun; Ye, Dan; Sun, Xuguang; Fang, Jiabei; Chu, Cuijiao; Feng, Tao; Jiang, Yiquan; Liang, Jin; Ren, Xuejuan; Zhang, Yaocun; Tang, Youmin
Abstract: Tippett (2019, https://doi.org/10.1029/2018JD029345 ) provides an insightful comment on the theoretical consideration part of Yang et al. (2018, https://doi.org/10.1029/2017JD028002 ), which studied the relationship between probabilistic and deterministic skills in dynamical seasonal climate prediction. The author connects the theoretical finding of Yang et al. (2018, https://doi.org/10.1029/2017JD028002 ) with some previous studies on this topic and further provide a simple‐form approximation to the derived theoretical relation in Yang et al. (2018, https://doi.org/10.1029/2017JD028002 ). However, the author also indicates the difference between the considerations in Yang et al. (2018, https://doi.org/10.1029/2017JD028002 ) and the previous studies. In this reply, we present a detailed explanation to the readers of the difference between these considerations. Key Points: The theoretical relationship in Yang et al. (2018) between probabilistic and deterministic skills is independent of whether the predictions are reliable or not